Effect of different running exercise modalities on post-exercise oxidative stress markers in trained athletes - Souissi, Wajdi; Bouzid, Mohamed Amine; Farjallah, Mohamed Amine; Ben Mahmoud, Lobna; Boudaya, Mariem; Engel, Florian; Sahnoun, Zouheir (International journal of environmental research and public health, 2020)
The aim of this study was to examine the effect of running exercise modality on oxidative stress. Thirteen endurance athletes (age: 21.46 ± 0.66 years) performed three different running exercise modalities (Continuous running exercise (CR): continuous running exercise at 75% of VO2max for 25 min; intermittent running exercise #1 (15/15): intermittent running protocol, 15 s running at 75% of VO2max, 15 s passive recovery, performed for 50 min; intermittent running exercise #2 (30/30): intermittent running protocol, 30 s running at 75% of VO2max, 30 s passive recovery, performed for 50 min) in a randomized order. Blood samples were drawn at rest and immediately after each running exercise and assessed for malondialdehyde (MDA), advanced oxidation protein products (AOPP), superoxide dismutase(SOD), and glutathione peroxidase (GPX) activities. MDA increased by 55% following 30/30 exercise (p < 0.01), while it remained unchanged with CR and15/15 exercise. SOD increased after CR (+13.9%, p < 0.05), and also remained unchanged after 15/15 (p > 0.05) and decreased after 30/30 (-19.7% p < 0.05). GPX and AOPP did not change after exercise in all experimental sessions (p > 0.05). In conclusion, 30/30 intermittent running induced higher lipid damages than the 15/15 and CR exercise. 15/15 intermittent exercise promoted a better balance between free radicals production and antioxidant defense compared to continuous exercise and intermittent 30/30 exercise.
Gesehen am 05.08.2020